Structural Vulnerability Among Migrating Women and Children Fleeing Central America and Mexico: The Public Health Impact of “Humanitarian Parole” - Valdez, Elizabeth Salerno; Valdez, Luis A.; Sabo, Samantha (Frontiers in Public Health, 2015)
Since October 2013, US Customs and Border Patrol has apprehended 15,979 families on the Southwest Border of the US. Daily, migrating women and children from Mexico and Central America that qualify for humanitarian parole are released from immigration detention to a humanitarian aid organization in Southern Arizona. After several days in detention facilities, these families arrive tired, hungry, dehydrated, and with minimal direction regarding their final destination, and adherence to the parameters of their parole. Project helping hands (PHHs) utilizes a network of volunteers to provide the women and children with food, water, clothing, hygiene products, hospitality, and legal orientation. The aim of this assessment was to document the experiences of families granted humanitarian parole through the lens of structural vulnerability. Here, we apply qualitative methods to elicit PHH lead volunteer perspectives regarding the migration experience of migrating families. Using inductive analysis, we found six major themes emerged from the qualitative data: reasons for leaving, experience on the journey, dehumanization in detention, family separation, vulnerability, and resiliency. These findings elucidate the different physical and psychological distresses that migrating families from Mexico and Central America experience before, during and after their arrival at the US–Mexico border. We posit that these distresses are a result of, or exacerbated by, structural vulnerability. Structural vulnerability has life-long health implications for a sub-population of young mothers and their children. The number of migrating families who have experienced traumatic events before and during their migration experience continues to expand and thus warrants consideration of mental health surveillance and intervention efforts for these families. More public health research is needed to better understand and combat the health challenges of this growing population.